Meningkatkan Hasil Belajar Matematika Siswa Melalui Pemanfaatan Media Buku Tiga Dimensi - Hamzah Upu; Muhammad Dinar; Hasdar H (Issues in Mathematics Education (IMED), 2017)
This research was the class action research that have the purpose to increase activities and mathematics learning result in the class VII.4 SMP Negeri 1 Tanete Riaja through the use of the media three dimension books with model of cooperative learning. The subject of this research is a class VII.4 SMP Negeri 1 Tanete Riaja with 27 people the number of students enrolled in academic year 2017/2018. This research was conducted within 2 cycles, the first cycle with 3 times and the second cycle with 4 times. In the implementation of learning with the use of three dimension books is an act that provided students to improve mathematics learning outcomes of students. The collect data were analyzed quantitatively and qualitatively. From the analysis it can be concluded that the results of students from class VII.4 junior high school of Tanete Riaja increased from cycle I to cycle II. After learning to use the three dimension books medium for two cylce of learning, obtained the following results: (1) The mathematics learning in the first cycle is at low categories, with an average score of 55,55. Highest score is 75 and lowest score is 15 of the maximum possible score is 100 with a standart deviation of 14,299. (2) The results of mathematics learning in the second cycle is the high category with an average 70,00. Highest score is 87,5 and lowest score is 35 of the maximum possible score is 100 with standart deviation of 14,839. (3) the qualitative analysis the changes occuring in the attitudes of students during the learning process in accordance with the observation that with the implementation of the learning model by using the three dimension books medium can increase interest in student learning and increase student attendance.